Ask questions and get helpful answers.

how would you simplify this equation:

y = (x+3)/[(4-sqrt(16+h))]

please help me!

you have three variables. I am not certain "simplify" is an appropriate term here.

ohhhh it was my mistake. I meant:

y = h/[(4-sqrt(16+h))]

y = h/[(4-sqrt(16+h))]
rationalize the denominator..

y = h/[(4-sqrt(16+h))] *(4+sqrt(16+h)/(4+sqrt(16+h)

y=h(4+sqrt(16+h)/(16-16-h)
you finish it. check my work.

  1. 👍
  2. 👎
  3. 👁
  4. ℹ️
  5. 🚩

Answer this Question

Related Questions

Still need help?

You can ask a new question or browse existing questions.